2016
DOI: 10.1152/ajprenal.00184.2016
|View full text |Cite
|
Sign up to set email alerts
|

The podocyte as a direct target for treatment of glomerular disease?

Abstract: The Centers for Disease Control and Prevention estimates more than 10% of adults in the United States, over 20 million Americans, have chronic kidney disease (CKD). A failure to maintain the glomerular filtration barrier directly contributes to the onset of CKD. The visceral epithelial cells, podocytes, are integral to the maintenance of this renal filtration barrier. Direct podocyte injury contributes to the onset and progression of glomerular diseases such as minimal change disease (MCD), focal segmental glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 63 publications
1
34
0
1
Order By: Relevance
“…Current therapy for primary FSGS is on the basis of immunosuppressive agents; it is now apparent that a number of these, including glucocorticoids and calcineurin inhibitors, directly modulate the podocyte phenotype (57). Recently, it has been shown that the effects of glucocorticoids may be mediated by Krüppel factor 15, a zinc finger transcription factor (57,58).…”
Section: Primary Fsgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current therapy for primary FSGS is on the basis of immunosuppressive agents; it is now apparent that a number of these, including glucocorticoids and calcineurin inhibitors, directly modulate the podocyte phenotype (57). Recently, it has been shown that the effects of glucocorticoids may be mediated by Krüppel factor 15, a zinc finger transcription factor (57,58).…”
Section: Primary Fsgsmentioning
confidence: 99%
“…Recently, it has been shown that the effects of glucocorticoids may be mediated by Krüppel factor 15, a zinc finger transcription factor (57,58). In a recent retrospective case series involving 476 subjects, the use of glucocorticoids and/or cyclosporin was associated with improved outcomes compared to no immunosuppression, with a hazard ratio of 0.49 (95% CI, 0.28 to 0.86) for ESRD whereas the use of cyclosporine with or without glucocorticoids was not associated with benefit HR 0.42 (95% CI, 0.15 to 1.18) (59).…”
Section: Primary Fsgsmentioning
confidence: 99%
“…This difference in the peak time can be explained by the slow release of PEGL carrier. Increased kidney weight caused by diabetes indicates renal hypertrophy, a common finding in the early stages of diabetes 25,26 . In this study, interstitial fibrosis, mesangial contraction, and structural remodeling contributed to the decrease in renal hypertrophy, and improved renal function reduced the 24-h urinary protein.…”
Section: Discussionmentioning
confidence: 99%
“…53 Podocytes constitute 21% to 34% of the total glomerular cell population, and podocytopathy can lead to minimal change disease, membranous nephropathy, focal and segmental glomerulosclerosis, membranous nephropathy, collapsing glomerulopathy, and diabetic nephropathy. 54,55 These are often the initiating cause of renal diseases that result in proteinuria and even ESRD. For these reasons, drug therapy directed to the MCs and podocytes is hypothesized to more effectively treat glomerular diseases than conventional nondirectional drug therapy.…”
Section: Renal Glomerulus As Targeting Sitementioning
confidence: 99%